2021
DOI: 10.1038/s41467-021-21550-4
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acids in pancreatic cancer cells drive tumour-associated macrophage differentiation via the Siglec receptors Siglec-7 and Siglec-9

Abstract: Changes in glycosylation during tumour progression are a key hallmark of cancer. One of the glycan moieties generally overexpressed in cancer are sialic acids, which can induce immunomodulatory properties via binding to Siglec receptors. We here show that Pancreatic Ductal Adenocarcinoma (PDAC) tumour cells present an increased sialylation that can be recognized by Siglec-7 and Siglec-9 on myeloid cells. We identified the expression of the α2,3 sialyltransferases ST3GAL1 and ST3GAL4 as main contributor to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 54 publications
12
133
0
1
Order By: Relevance
“…Authors identified ST3GAL1 and ST3GAL4 as the main contributors to the synthesis of ligands for Siglec-7 and Siglec-9 in tumor cells. Tumor-derived sialic acids force monocytes to produce IL-10 and IL-6 and subsequently drive their differentiation to immune suppressive TAMs through the activation of the Siglec-9 receptor [93] (Table 3).…”
Section: Promoting Immune Evasionmentioning
confidence: 99%
“…Authors identified ST3GAL1 and ST3GAL4 as the main contributors to the synthesis of ligands for Siglec-7 and Siglec-9 in tumor cells. Tumor-derived sialic acids force monocytes to produce IL-10 and IL-6 and subsequently drive their differentiation to immune suppressive TAMs through the activation of the Siglec-9 receptor [93] (Table 3).…”
Section: Promoting Immune Evasionmentioning
confidence: 99%
“…The recent study by Rodriguez [ 104 ] identified monocyte-derived macrophages, whose differentiation was induced via signaling through Siglec-7 and Siglec-9 as a consequence of the enhanced sialylation, as contributors to the poor clinical outcome in pancreatic ductal adenocarcinoma (PDAC) tumor. Moreover, Sias can target different myeloid cells, as demonstrated by the diminishment in inflammatory response induced by Siglec-9 and the upregulation of programmed death ligand-1 (PD-L1) and IL-10 expression [ 104 ].…”
Section: Sialic Acid-siglec Interactions In Human Diseasesmentioning
confidence: 99%
“…The upregulation of sialic acid-containing glycans in the tumor microenvironment, termed tumor hypersialylation, contributes to the establishment of an immunosuppressive milieu and dampens anti-tumor immune responses via the engagement of immunomodulatory Siglecs expressed on tumor-infiltrating immune cells 4,5 . Recent work has suggested the sialoglycan-Siglec axis as a new immune checkpoint that can be targeted to drive innate and adaptive anti-tumor immunity 4,[6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of inhibitory CD33-related Siglecs, including human Siglec-7/-9 and murine Siglec-E, on tumor-associated macrophages (TAMs) was shown to support cancer progression by driving macrophage polarization towards the tumor-promoting M2 phenotype 4,9,13 . Similarly, NK cell-mediated killing of tumor cells can be blocked in a dose-dependent manner by the interactions between tumor sialoglycans and Siglec-7/-9 on human NK cells 7,11 .…”
Section: Introductionmentioning
confidence: 99%